INFLUENCE OF MATERNAL IRON DEFICIENCY ANEMIA ON MORPHOMETRIC STATE OF LIVER OF FETUSES AND NEWBORNS - Проценко, О.С. (World of Medicine and Biology, 2014)
Among extragenital disorders of pregnant women, according to various authors, in 21-80% of cases iron deficiency anemia (IDA) is registered. Maternal IDA leads to the development of placental insufficiency leading to fetal hypoxia and adverse effects on the formation and function of many organs and tissues. Stellate reticuloendotheliocytes (SRE), or Kupffer cells, are macrophages by their origin, structure, and function, and make up 80-90% of the fixed macrophages of the reticuloendothelial system (RES). SRE are important in the regulation of the structural homeostasis of the liver, affect the growth and regeneration of hepatocytes, maintain immunological homeostasis, are involved in iron metabolism, synthesis of erythropoietin, etc. Data on morphometric and morpho-functional features of liver SRE in fetuses and newborns from mothers with IDA are absent. It should be noted that the formation of the liver in the antenatal period determines not only the development of adaptive mechanisms in the postnatal period, but could be the basis for further development of hepatocellular diseases of children and adults. The aim of this study was to investigate the morphometric features of liver SRE in fetuses and newborns born from mothers with anemia. This research is based on a study of liver of fetuses and newborns born from mothers whose pregnancy was complicated by iron deficiency anemia. Depending on the severity of maternal anemia entire experimental material was divided into the following observable groups: A1 - newborns of mothers with mild anemia (18 cases), A2 - newborns from mothers with anemia of moderate severity (26 cases), A3 - newborns from mothers with severe anemia (27 cases). The control group (C) consisted of newborns, bred in the conditions of physiological pregnancy and died as a result of acute disturbance of utero-placental and umbilical cord blood circulation (22 cases). In the control group detected histologically stored beams of the structure of the liver. In the central veins of the liver lobules founded moderately severe hyperemia and moderate expansion of the capillaries. In the fetal liver from mothers with mild anemia significant morphological differences compared with the control group were not detected, but hyperemia of the capillaries and central veins is more marked. In SRE significantly increased the diameter of the cells and reduced nuclear-cytoplasmic ratio by increasing the volume of the cytoplasm compared with the control group. In the liver of fetuses and newborns A2 groups marked central venous plethora, the expansion of space of Disse, moderate discomplexation of radial structure of gulches, atomizing fatty degeneration of hepatocytes. Marked proliferation of SRE, which is larger in comparison with the control group and A1 group, with lots of pseudopodia, optically dense cytoplasm, with increased response to RNP and reduction reactions at the DNP. In SRE significantly reduced diameter, nuclear volume, nuclear-cytoplasmic ratio, and significantly increased diameter and the volume of the cell as compared with a control group and a group A1 by increasing the volume of the cytoplasm. In the liver of fetuses and newborns of A3 groups is detected more pronounced fatty degeneration of hepatocytes, the appearance of hypertrophic single- and binuclear hepatocytes on the periphery of the lobule, and wrinkled hepatocytes with fragmented nuclei in the middle third of the lobule and sometimes in the center of the lobule. There is a massive proliferation of the SRE, however, most cells do not have pseudopodia, their light cytoplasm and nucleus are fragmented. In SRE significantly reduced diameter, the volume of the cells as compared to the control group and all comparison groups by reducing the volume of the cytoplasm. On the other hand, there is a significant increase in the nuclear-cytoplasmic ratio, diameter and volume of the nucleus on account of their swelling. With maternal IDA on the background of developing feto-placental insufficiency and chronic fetal hypoxia, marked increase in degenerative changes of hepatocytes of the liver of fetuses and newborns of varying severity, which documented predominantly periportal, suggesting that these departments are responding to hypoxia in the first place. The increase of venous plethora and the expansion of space of Disse of liver of fetuses and newborns is directly proportional to the severity of maternal iron deficiency anemia, which is also a consequence and a manifestation of chronic intrauterine hypoxia. With maternal IDA of moderate severity observed hyperplasia of SRE with activation of their macrophage activity, which is manifested by increasing their size by increasing the morphometric and optical parameters of the cytoplasm and increased pseudopodia. In severe degree of maternal IDA SRE of liver of fetuses and newborns are also hyperplastic, however, a decrease in cell size due to the morphometric and optical parameters of the cytoplasm, the absence of pseudopodia indicates the depletion of their morphological and functional activity. It can be assumed that the increased activation of SRE with maternal anemia of moderate severity leads to their functional depletion with further increase of the severity of maternal IDA. Conclusions: Maternal IDA has an adverse effect on the morphological state of the liver parenchyma of fetuses and newborns, causing the development of venous plethora and degenerative changes of hepatocytes. In maternal IDA of moderate severity maximally expressed adaptive mechanisms SRE in the form of hyperplasia, hypertrophy, and signs of active metabolism of DNP and RNP.In severe maternal IDA adaptive mechanisms of SRE depleted in the form of hypoplasia, loss of pseudopodia and signs of depression of metabolism in DNP and RNP.